Propriedades de fibrocimentos extrudados reforçados com diferentes concentrações de resíduo de cigarros - Faria, Alysson Siqueira (2022)
In this work had as objective to evaluate the residue cigarettes use effect on the physical and mechanical properties of extruded fiber cements. The experimental design consists of 6 treatments and 5 percentages being evaluated replacing Portland cement for cigarette residue (0, 1, 2, 3, 4 and 5%). Lignocellulosic fibers from cigarette residue were evaluated as morphological and physical characteristics. The extruded fiber cements were made from the following control composition: 70% Portland cement CPV-ARI, 30% limestone, 1% HPMC additive, 1% ADVA additive, and water ratio: cement 0.30. The other treatments replaced the cement for cigarettes residue 1 to 5%. Composites dimensions produced were 200 mm x 50 mm x 15 mm (length, width and thickness, respectively). The compounds were produced by the extrusion method and were applied for 28 days in a plastic container with saturated moisture, without sun exposure, at the UFLA composite laboratory. The curing inhibition index of cementitious mass was evaluated, and later, cigarette residue treatment was carried out to minimize inhibition of cement curing. The dimensional, physical and mechanical properties of the extruded fiber cements were also evaluated. All treatments introduced meet the requirements of regulatory standards for water absorption (physical property) and for the rupture modulus (mechanical property) except the treatment with 5% replacement of cement for tobacco residue, which reached a value lower than 4Mpa for the MOR, not complying with the minimum value required by the standards, mainly due to the strong influence of the extractives contained in the residue of the lignocellulosic material even after the treatment. It is technically feasible to use until 4% tobacco residue to replace the cement mass for the extruded fiber cements production with 28 days of curing; missing to evaluate, physical and mechanical properties of the extruded fiber cements after the accelerated aging, so that it can be produced on an industrial scale.